Tingkat Pengetahuan Pustakawan terhadap Brand Identity Perpustakaan - Wijayanti, Nova Indah; Mustar, Maniso (Forum Perpustakaan Perguruan Tinggi Indonesia, 2023)
Libraries, as educational and cultural institutions, face various challenges and changes. One of the ways to enhance the reputation of libraries is through branding as a reliable access to information. Library branding goes beyond more than identity or a level of awareness. It aims to improve the continuous experience of library users. Brand identity is often perceived primarily through visual aspects such as logos, colors, shapes, and visual identification. Vision, Mission, core values, organizational culture, and competencies are vital elements of the internal component of corporate branding. This study examined librarian’s knowledge levels regarding brand identity using three corporate communication elements: communication, behavior, and symbolism. The total population is more than 100 with a confidence level of 90% and a 10% margin of error, namely 40 librarians—data collection targeting librarians and the staff in a university library. The validity test results were from 15 questions; 13 were valid, and 2 were invalid. The reliability test stated that this study was reliable. The results showed that the level of knowledge of librarians for communication got a score of 3,92, which means high. Behavior got a score of 4,47, which means very high, and symbolism got a score of 3,57, which means high. The mean total score is 3,57, which is high. The conclusion is that the librarian’s level of knowledge about brand identity is high. The most influential factor for internal brand identity in this study is behavior.